Parental hopes, interventions, and survival of neonates with trisomy 13 and trisomy 18. Issue 3 (23rd August 2016) - Janvier, Annie; Farlow, Barbara; Barrington, Keith J.
Abstract : Trisomy 13 and 18 are life‐limiting conditions for which a palliative approach is frequently recommended. The objective of this study was to examine parental goals/decisions, the length of life of their child and factors associated with survival. Parents of children who lived with trisomy 13 or 18 that were part of English‐speaking social networks were invited to participate in a questionnaire study. Participants answered questions about their hopes/goals, decisions regarding neonatal interventions, and the duration of their children's lives. The participants were 332 parents who answered questions about their 272 children (87% response rate based on site visits; 67% on invitations sent). When parents were asked about their hope after the diagnosis, the main themes invoked by parents were the following: meet their child alive (80% of parents with a prenatal diagnosis), spend some time as a family (72%), bring their child home (52%), and give their child a good life (66%). Parents wanted to give them a chance, but also reported their fears were medical complexity, pain and/or life in the hospital (61%). Healthcare providers recommended comfort care at birth to all parents. Life‐sustaining interventions "as for any other child" was chosen as a plan of care by 25% of parents. Of the 216 children with full trisomy, 69% were discharged home after birth and 40% lived >1 y. The presence of a prenatal diagnosis was the strongest independent factor negatively associated with longevity: 36% of children with a prenatal diagnosis lived <24 hr and 47% were discharged home compared to 1% and 87%, respectively for children with a postnatal diagnosis ( P  < 0.01). Male gender, low‐birth weight, and cardiac and/or cerebral anomaly were also associated with decreased survival ( P  < 0.05). After a prenatal diagnosis, palliative care at birth consisted of limited interventions, whereas after a postnatal diagnosis (median age of 6 days) it consisted of various interventions, including oxygen, ventilation, tube feeding and intravenous fluids, complicating the analysis. In conclusion, the goals of parents of children with trisomy 13 or 18 were to meet their child, be discharged home and be a family. Having a postnatal diagnosis was the independent factor most associated with these goals. Children with a postnatal diagnosis were treated "as any other children" until the diagnosis, which may give them a survival advantage, independent of palliative care. Rigorous transparency regarding specific interventions and outcomes may help personalize care for these children. © 2016 Wiley Periodicals, Inc.